Method for preparing surface high-entropy metallized layer to assist brazing of large-size ceramic matrix composite and niobium joint based on Joule thermal shock
By using Joule thermal shock on the surface of the C/SiC composite material, the residual stress problem caused by CTE differences during the brazing process is solved, and the high strength and toughness of the joint is achieved, which is suitable for high temperature environments.
Patent Information
- Application Number
- CN202510034964.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The difference in CTE between C/SiC composite and niobium leads to greater residual stress during the brazing process, affecting the fatigue life and safety and reliability of the joint.
The method of preparing the surface high-entropy metallization layer based on Joule thermal shock is adopted. By depositing a high-entropy alloy layer on the surface of C/SiC composite materials, a stress buffer zone is formed, residual stress is reduced, and weld structure is optimized.
It effectively alleviates the problem of the difference in thermal expansion coefficient between ceramics and metals, reduces the residual stress of the joint, improves the toughness and strength of the joint, extends the fatigue life, and is suitable for high-temperature conditions.
Smart Images

Figure CN119634862A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of brazing. Background Art
[0002] In modern aerospace propulsion systems, rocket engine nozzles are one of the key components, and their material selection and connection technology are crucial to the overall performance of the engine. C / SiC composites have become one of the ideal materials for the nozzles of the new generation of rocket engines due to their excellent mechanical properties, low density and good chemical stability. Due to the poor processing performance of C / SiC composites, C / SiC composites are usually connected to metal materials such as metal niobium (Nb) through brazing technology in applications. In this process, the significant CTE difference between C / SiC and niobium leads to large residual stress during brazing, especially for large-sized joints, where the stress increases exponentially. Long-term residual stress will not only reduce the fatigue life of the joint, but may also cause crack initiation and expansion, thereby affecting the safety and reliability of the nozzle and even the entire engine.
[0003] In recent years, surface metallization technology has been proposed as an effective solution, aiming to improve the interfacial compatibility between ceramic materials and metal substrates by depositing a metal coating on the surface of ceramic materials, thereby reducing residual stress. High entropy alloys are considered to be ideal metallization materials due to their excellent comprehensive mechanical properties, good corrosion resistance and high temperature stability. However, the high melting point characteristics of high entropy alloys limit the application scope of traditional metallization processes, especially when processing large components, which faces more challenges. Summary of the invention
[0004] The present invention aims to solve the problem of excessive residual stress in the existing brazing connection between C / SiC composite materials and niobium, and further provides a method for preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing large-sized ceramic-based composite materials and niobium joints.
[0005] A method for preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing a large-size ceramic matrix composite material and a niobium joint is carried out in the following steps:
[0006] 1. Coating alloy mixture:
[0007] The FeCoCrNiMo alloy powder and the N-methylpyrrolidone solution of polyvinylidene fluoride are stirred and mixed until they are viscous to obtain an alloy mixture, and the alloy mixture is applied to a surface of the C / SiC composite material that is perpendicular to the growth direction of the carbon fibers to obtain a C / SiC composite material coated with the mixture;
[0008] 2. High entropy alloying on the surface of C / SiC composites:
[0009] Under the conditions of a metallization voltage of 25V to 35V and a metallization current of 40A to 60A, the C / SiC composite material coated with the mixed solution is heated for 10s to 20s to form a high entropy alloy layer, and then the high entropy alloy layer is polished and cleaned to obtain a C / SiC composite material with a high entropy alloy layer;
[0010] 3. Assembly of parts to be welded:
[0011] Assembling in order from bottom to top: metal niobium, AgCuTi solder sheet, and C / SiC composite material with high entropy alloy layer, and the high entropy alloy layer of the C / SiC composite material with high entropy alloy layer is bonded to the AgCuTi solder sheet to obtain a workpiece to be welded;
[0012] 4. Vacuum brazing:
[0013] The parts to be welded are placed in a vacuum brazing furnace and evacuated. They are first kept warm for 5 to 20 minutes at 100 to 200 degrees Celsius, then kept warm for 5 to 20 minutes at 800 to 950 degrees Celsius, and finally cooled to room temperature. This completes the method for preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing large-size ceramic-based composite materials and niobium joints.
[0014] The beneficial effects of the present invention are:
[0015] 1. The method of the present invention can effectively alleviate the problem of a large difference in thermal expansion coefficients between ceramics and metallic niobium. Too large a difference in thermal expansion coefficients will lead to excessive residual stress in the joint, which will eventually cause cracks in the joint. By adding a high-entropy alloy surface metallization layer to the surface of the C / SiC composite material, the Joule thermal shock energy can significantly increase the lattice distortion of the high-entropy alloy, improve the plastic deformation ability, form a stress buffer zone, and alleviate the residual stress of the joint to prevent the generation of cracks.
[0016] 2. The method of the present invention can form a buffer metal layer in the internal area of the ceramic joint to alleviate the difference in thermal expansion coefficient by adding a high entropy alloy surface metallization layer, thereby regulating the distribution of residual stress in the overall weld joint. On the other hand, the high entropy alloy surface metallization layer reduces the growth of brittle compounds on the ceramic joint side, optimizes the weld structure of the silver-copper-titanium (AgCuTi) solder, and improves the plasticity and toughness of the weld; a good solid solution structure is formed in the joint, thereby improving the toughness and strength of the joint.
[0017] 3. The present invention utilizes a high entropy metallization layer to effectively improve the wettability and bonding strength between the solder and the ceramic composite material, thereby ensuring good connection between the large-sized ceramic composite material and the niobium-based solder.
[0018] 4. Realizing high entropy metallization of the surface of C / SiC composite materials usually requires a high metallization temperature. The Joule thermal shock of the present invention can reach an extremely high temperature in a short time and quickly cool down, reducing the damage to the parent material caused by long-term heating of traditional metallization. Moreover, Joule thermal shock can effectively improve the problem of the overly thick brittle compound reaction layer generated between the metallization layer and the C / SiC composite material. The thickness of the interface reaction layer is relatively thin, which greatly improves the mechanical properties of the joint.
[0019] 5. The present invention utilizes high entropy alloy as the ceramic surface metallization layer to assist the AgCuTi solder joint, and the corresponding room temperature shear strength is 177 MPa, which is 2.3 times that of the surface unmetallized ceramic joint (77 MPa). At the same time, the joint has good high temperature performance, and the shear strength at 500°C is 102 MPa, which is suitable for service environment under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Transmission electron microscope images and geometric phase analysis diagrams of the high entropy metallization layer in the C / SiC composite material with a high entropy alloy layer prepared in step 2 of Example 1, (a) TEM of a typical solid solution structure of a high entropy alloy, (b) electron diffraction spots of the solid solution structure, (c) TEM geometric phase analysis;
[0021] Figure 2 This is a scanning electron microscope photo of the joint of the C / SiC composite material-niobium weldment prepared in Example 1;
[0022] Figure 3 Figures 1 and 2 are joint test data of C / SiC composite material-niobium weldments prepared in Examples 1 to 3 and comparative experiments, (a) room temperature joint strength corresponding to different high entropy layer thicknesses, (b) joint strength of C / SiC composite material-niobium weldments prepared in Example 1 at room temperature and 500°C, (c) joint shear stress-strain curve, 1 is the stress-strain curve of room temperature joint strength of C / SiC composite material-niobium weldments prepared in the comparative experiment, 2 is the stress-strain curve of room temperature joint strength of C / SiC composite material-niobium weldments prepared in Example 1, and 3 is the stress-strain curve of joint strength of C / SiC composite material-niobium weldments prepared in Example 1 at 500°C. DETAILED DESCRIPTION
[0023] Specific implementation method 1: This implementation method is a method for preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing a large-sized ceramic-based composite material and a niobium joint, which is carried out in the following steps:
[0024] 1. Coating alloy mixture:
[0025] The FeCoCrNiMo alloy powder and the N-methylpyrrolidone solution of polyvinylidene fluoride are stirred and mixed until they are viscous to obtain an alloy mixture, and the alloy mixture is applied to a surface of the C / SiC composite material that is perpendicular to the growth direction of the carbon fibers to obtain a C / SiC composite material coated with the mixture;
[0026] 2. High entropy alloying on the surface of C / SiC composites:
[0027] Under the conditions of a metallization voltage of 25V to 35V and a metallization current of 40A to 60A, the C / SiC composite material coated with the mixed solution is heated for 10s to 20s to form a high entropy alloy layer, and then the high entropy alloy layer is polished and cleaned to obtain a C / SiC composite material with a high entropy alloy layer;
[0028] 3. Assembly of parts to be welded:
[0029] Assembling in order from bottom to top: metal niobium, AgCuTi solder sheet, and C / SiC composite material with high entropy alloy layer, and the high entropy alloy layer of the C / SiC composite material with high entropy alloy layer is bonded to the AgCuTi solder sheet to obtain a workpiece to be welded;
[0030] 4. Vacuum brazing:
[0031] The parts to be welded are placed in a vacuum brazing furnace and evacuated. They are first kept warm for 5 to 20 minutes at 100 to 200 degrees Celsius, then kept warm for 5 to 20 minutes at 800 to 950 degrees Celsius, and finally cooled to room temperature. This completes the method for preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing large-size ceramic-based composite materials and niobium joints.
[0032] The beneficial effects of this embodiment are:
[0033] 1. The method of this embodiment can effectively alleviate the problem of a large difference in thermal expansion coefficients between ceramics and metallic niobium. Too large a difference in thermal expansion coefficients will lead to excessive residual stress in the joint, which will eventually cause cracks in the joint. By adding a high-entropy alloy surface metallization layer to the surface of the C / SiC composite material, the Joule thermal shock energy can significantly increase the lattice distortion of the high-entropy alloy, improve the plastic deformation ability, and form a stress buffer zone, which can alleviate the residual stress of the joint and prevent the occurrence of cracks.
[0034] 2. The method of this embodiment can form a buffer metal layer in the internal area of the ceramic joint to alleviate the difference in thermal expansion coefficient by adding a high entropy alloy surface metallization layer, thereby regulating the distribution of residual stress in the overall weld joint. On the other hand, the high entropy alloy surface metallization layer reduces the growth of brittle compounds on the ceramic joint side, optimizes the weld structure of silver-copper-titanium (AgCuTi) solder, and improves the plasticity and toughness of the weld; a good solid solution structure is formed in the joint, which improves the toughness and strength of the joint.
[0035] 3. This embodiment utilizes a high entropy metallization layer to effectively improve the wettability and bonding strength between the solder and the ceramic composite material, thereby ensuring a good connection between the large-sized ceramic composite material and the niobium-based solder.
[0036] 4. Realizing high entropy metallization of the surface of C / SiC composite materials usually requires a high metallization temperature. The Joule thermal shock of this embodiment can reach an extremely high temperature in a short time and cool down quickly, reducing the damage to the parent material performance caused by long-term heating of traditional metallization. Moreover, Joule thermal shock can effectively improve the problem of the excessively thick brittle compound reaction layer generated between the metallization layer and the C / SiC composite material. The thickness of the interface reaction layer is relatively thin, which greatly improves the mechanical properties of the joint. 5. This embodiment uses high entropy alloy as the ceramic surface metallization layer to assist the AgCuTi solder joint. The corresponding room temperature shear strength is 177MPa, which is 2.3 times that of the surface unmetallized ceramic joint (77MPa). At the same time, the joint has good high temperature performance, and the shear strength at 500°C is 102MPa, which is suitable for service environments under high temperature conditions.
[0037] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the concentration of the N-methylpyrrolidone solution of polyvinylidene fluoride described in step 1 is 0.05 g / L to 0.2 g / L. Other aspects are the same as those of specific embodiment 1.
[0038] Specific embodiment 3: This embodiment is different from specific embodiment 1 or 2 in that the mass ratio of FeCoCrNiMo alloy powder to polyvinylidene fluoride in the alloy mixture in step 1 is (1-10): 1. The rest is the same as specific embodiment 1 or 2.
[0039] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the stirring and mixing to a viscous state in step 1 is specifically stirring for 5 to 20 minutes at a rotation speed of 300 to 1000 rpm. The rest is the same as specific embodiment 3.
[0040] Specific embodiment 5: This embodiment differs from Specific embodiments 1 to 4 in that the thickness of the high entropy alloy layer in the C / SiC composite material with a high entropy alloy layer described in step 2 is 50 μm to 300 μm. Other aspects are the same as Specific embodiments 1 to 4.
[0041] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: the C / SiC composite material described in step 1 is a pretreated C / SiC composite material, and the pretreatment is specifically to use ethanol ultrasonic assisted cleaning for 5min to 15min under the condition of power of 50W to 200W; the polishing and cleaning of the high entropy alloy layer described in step 2 is specifically to use 3000# sandpaper to polish the surface of the high entropy alloy layer to a thickness of 50μm to 300μm, and then use ethanol ultrasonic assisted cleaning for 5min to 15min under the condition of power of 50W to 200W. The rest is the same as specific embodiments 1 to 5.
[0042] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that the thickness of the AgCuTi solder sheet in step 3 is 100 μm to 500 μm. The rest is the same as specific embodiments 1 to 6.
[0043] Specific embodiment eight: This embodiment is different from specific embodiments one to seven in that: the metal niobium described in step three is the pretreated metal niobium, and the pretreatment is to use 180#, 400# and 800# sandpaper to remove the oxide film on the surface of the metal niobium, and then use ethanol ultrasonic assisted cleaning for 5min to 15min under the condition of power of 50W to 200W; the AgCuTi solder sheet described in step three is the pretreated AgCuTi solder sheet, and the pretreatment is specifically carried out according to the following steps: use 500# sandpaper to polish the AgCuTi solder sheet to remove the surface oxide, and then use ethanol ultrasonic assisted cleaning for 5min to 15min under the condition of power of 50W to 200W. The rest is the same as specific embodiments one to seven.
[0044] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: in step 4, vacuum is drawn to 1×10 -4 Pa~1×10 -5 Pa. The rest is the same as the first to eighth embodiments.
[0045] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that: in step 4, the temperature is raised to 100°C to 200°C at a heating rate of 5°C / min to 10°C / min, and the temperature is kept at 100°C to 200°C for 5min to 20min, then the temperature is raised to 800°C to 950°C at a heating rate of 5°C / min to 10°C / min, and the temperature is kept at 800°C to 950°C for 5min to 20min, and finally the temperature is cooled to room temperature at a cooling rate of 5°C / min to 10°C / min. The rest is the same as specific embodiments 1 to 9.
[0046] The following examples are used to verify the beneficial effects of the present invention:
[0047] Embodiment 1:
[0048] A method for preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing a large-size ceramic matrix composite material and a niobium joint, which is carried out in the following steps:
[0049] 1. Coating alloy mixture:
[0050] Under the condition of a rotation speed of 300 rpm, FeCoCrNiMo alloy powder and N-methylpyrrolidone solution of polyvinylidene fluoride were stirred and mixed for 10 minutes until they became viscous to obtain an alloy mixture, and the alloy mixture was coated on a surface of the C / SiC composite material perpendicular to the growth direction of the carbon fiber to obtain a C / SiC composite material coated with the mixture;
[0051] The size of the C / SiC composite material is 50 mm×50 mm×50 mm; the ratio of each element in the FeCoCrNiMo alloy powder (purchased) is 1:1:1:1:1; the concentration of the N-methylpyrrolidone solution of polyvinylidene fluoride is 0.1 g / L; the mass ratio of the FeCoCrNiMo alloy powder to polyvinylidene fluoride in the alloy mixture is 4:1;
[0052] 2. High entropy alloying on the surface of C / SiC composites:
[0053] The C / SiC composite material coated with the mixed solution is placed in a thermal shock device, and the C / SiC composite material coated with the mixed solution is heated for 15 seconds under the conditions of a metallization voltage of 31V and a metallization current of 50A to form a high entropy alloy layer, and then the high entropy alloy layer is polished and cleaned to obtain a C / SiC composite material with a high entropy alloy layer;
[0054] The thickness of the high entropy alloy layer in the C / SiC composite material having a high entropy alloy layer is 150 μm;
[0055] 3. Assembly of parts to be welded:
[0056] Assembling in order from bottom to top: metal niobium, AgCuTi solder sheet, and C / SiC composite material with high entropy alloy layer, and the high entropy alloy layer of the C / SiC composite material with high entropy alloy layer is bonded to the AgCuTi solder sheet to obtain a workpiece to be welded;
[0057] The size of the metal niobium is 100mm×100mm×50mm; the thickness of the AgCuTi solder sheet is 400μm; the mass percentage of Ag in the AgCuTi solder sheet is 68.8%, the mass percentage of Cu is 26.7%, and the mass percentage of Ti is 4.5%;
[0058] 4. Vacuum brazing:
[0059] Place the parts to be welded in a vacuum brazing furnace and evacuate to 1×10 -4 Pa, firstly heated to 150°C at a heating rate of 10°C / min, and kept at 150°C for 10 min, then heated to 880°C at a heating rate of 10°C / min, and kept at 880°C for 10 min, and finally cooled to room temperature at a cooling rate of 5°C / min to obtain a C / SiC composite material-niobium welded part.
[0060] The C / SiC composite material described in step 1 is a pretreated C / SiC composite material, wherein the pretreatment is specifically performed by using ethanol ultrasonic assisted cleaning for 10 minutes at a power of 100 W;
[0061] The polishing and cleaning of the high entropy alloy layer in step 2 specifically includes polishing the surface of the high entropy alloy layer to a thickness of 150 μm using 3000# sandpaper, and then using ethanol ultrasonic assisted cleaning for 10 minutes at a power of 100 W;
[0062] The metal niobium described in step three is the pretreated metal niobium, and the pretreatment is specifically to remove the oxide film on the surface of the metal niobium with 180#, 400# and 800# sandpaper in sequence, and then use ethanol ultrasonic assisted cleaning for 10 minutes at a power of 100W; the AgCuTi solder sheet described in step three is the pretreated AgCuTi solder sheet, and the pretreatment is specifically carried out according to the following steps: use 500# sandpaper to polish the AgCuTi solder sheet to remove the surface oxide, and then use ethanol ultrasonic assisted cleaning for 10 minutes at a power of 100W.
[0063] Embodiment 2: This embodiment is different from Embodiment 1 in that the thickness of the high entropy alloy layer in the C / SiC composite material with the high entropy alloy layer described in step 2 is 50 μm. Other aspects are the same as those of Embodiment 1.
[0064] Embodiment 3: This embodiment is different from Embodiment 1 in that the thickness of the high entropy alloy layer in the C / SiC composite material with the high entropy alloy layer described in step 2 is 300 μm. Other aspects are the same as those of Embodiment 1.
[0065] Comparative experiment: The difference between this comparative experiment and Example 1 is that step 1 and step 2 are omitted, and in step 3, metal niobium, AgCuTi solder sheet and C / SiC composite material are assembled in order from bottom to top to obtain the welded part. The rest is the same as Example 1.
[0066] Figure 1 Transmission electron microscope images and geometric phase analysis diagrams of the high entropy metallization layer in the C / SiC composite material with a high entropy alloy layer prepared in step 2 of Example 1, (a) typical solid solution structure TEM of high entropy alloy, (b) electron diffraction spots of solid solution structure, (c) TEM geometric phase analysis; it can be seen from the figure that the electron diffraction spots have linear strip-shaped spots. In the geometric phase analysis diagram, red represents tensile strain and blue represents compressive strain. Both figures indicate that there is a large lattice distortion in the high entropy metallization layer.
[0067] Figure 2 This is a scanning electron microscope photo of the joint of the C / SiC composite material-niobium weldment prepared in Example 1. As can be seen from the figure, the joint interface obtained by the method of Example 1 is good, no cracks are generated on the interface, a uniform solid solution structure is formed in the joint, there is no obvious continuous brittle compound phase, and a reliable connection is formed.
[0068] According to the GB / T 22617-2008 test standard, the C / SiC composite material-niobium welded parts prepared in Examples 1 to 3 and the comparative experiment were tested; Figure 3Figures 1 and 2 are joint test data of C / SiC composite material-niobium weldments prepared in Examples 1 to 3 and comparative experiments, (a) room temperature joint strength corresponding to different high entropy layer thicknesses, (b) joint strength of C / SiC composite material-niobium weldments prepared in Example 1 at room temperature and 500°C, (c) joint shear stress-strain curve, 1 is the stress-strain curve of room temperature joint strength of C / SiC composite material-niobium weldments prepared in comparative experiments, 2 is the stress-strain curve of room temperature joint strength of C / SiC composite material-niobium weldments prepared in Example 1, and 3 is the stress-strain curve of joint strength of C / SiC composite material-niobium weldments prepared in Example 1 at 500°C; it can be seen from the figure that the room temperature shear strength corresponding to the brazing joint of Example 1 is 177MPa, which is 2.3 times that of the non-metallized ceramic joint (77MPa) on the surface of the comparative experiment. At the same time, the joint has good high temperature performance, and the shear strength tested at 500°C is 102MPa, which is suitable for service environments under high temperature conditions. From the stress-strain curve of the joint, it can be seen that when there is no high entropy layer, the fracture mode of the joint at room temperature is brittle fracture, the joint fails quickly, and the fracture stroke is only 10%. After adding the high entropy layer, the fracture mode of the joint at room temperature is transformed into ductile fracture, the fracture stroke is 27%, and the joint does not fail quickly, but the mechanical properties slowly decrease, and it also shows the characteristics of ductile fracture at 500℃, indicating that the joint has good service ability at high temperature.
Claims
1. A method for preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing a large-size ceramic matrix composite material and a niobium joint, characterized in that It is carried out in the following steps:
1. Coating alloy mixture: The FeCoCrNiMo alloy powder and the N-methylpyrrolidone solution of polyvinylidene fluoride are stirred and mixed until they are viscous to obtain an alloy mixture, and the alloy mixture is applied to a surface of the C / SiC composite material that is perpendicular to the growth direction of the carbon fibers to obtain a C / SiC composite material coated with the mixture; 2. High entropy alloying on the surface of C / SiC composites: Under the conditions of a metallization voltage of 25V to 35V and a metallization current of 40A to 60A, the C / SiC composite material coated with the mixed solution is heated for 10s to 20s to form a high entropy alloy layer, and then the high entropy alloy layer is polished and cleaned to obtain a C / SiC composite material with a high entropy alloy layer; 3. Assembly of parts to be welded: Assembling in order from bottom to top: metal niobium, AgCuTi solder sheet, and C / SiC composite material with high entropy alloy layer, and the high entropy alloy layer of the C / SiC composite material with high entropy alloy layer is bonded to the AgCuTi solder sheet to obtain a workpiece to be welded; 4. Vacuum brazing: The parts to be welded are placed in a vacuum brazing furnace and evacuated. They are first kept warm for 5 to 20 minutes at 100 to 200 degrees Celsius, then kept warm for 5 to 20 minutes at 800 to 950 degrees Celsius, and finally cooled to room temperature. This completes the method for preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing large-size ceramic-based composite materials and niobium joints.
2. The method of preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing a large-size ceramic matrix composite material and a niobium joint according to claim 1, characterized in that The concentration of the polyvinylidene fluoride N-methylpyrrolidone solution described in step 1 is 0.05 g / L to 0.2 g / L.
3. The method of preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing a large-size ceramic matrix composite material and a niobium joint according to claim 1, characterized in that The mass ratio of FeCoCrNiMo alloy powder to polyvinylidene fluoride in the alloy mixture described in step 1 is (1-10):
1.
4. The method of preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing a large-size ceramic matrix composite material and a niobium joint according to claim 1, characterized in that The stirring and mixing in step 1 until the mixture becomes viscous is specifically performed at a rotation speed of 300 rpm to 1000 rpm for 5 min to 20 min.
5. The method of preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing a large-size ceramic matrix composite material and a niobium joint according to claim 1, characterized in that The thickness of the high entropy alloy layer in the C / SiC composite material with a high entropy alloy layer described in step 2 is 50 μm to 300 μm.
6. The method of preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing a large-sized ceramic matrix composite material and a niobium joint according to claim 1, characterized in that The C / SiC composite material described in step 1 is a pretreated C / SiC composite material, and the pretreatment is specifically performed under a power of 50W to 200W, using ethanol ultrasonic assisted cleaning for 5min to 15min; the polishing and cleaning of the high entropy alloy layer described in step 2 is specifically performed using 3000# sandpaper to polish the surface of the high entropy alloy layer to a thickness of 50μm to 300μm, and then using ethanol ultrasonic assisted cleaning for 5min to 15min under a power of 50W to 200W.
7. The method of preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing a large-size ceramic matrix composite material and a niobium joint according to claim 1, characterized in that The thickness of the AgCuTi solder sheet described in step 3 is 100 μm to 500 μm.
8. The method of preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing a large-size ceramic matrix composite material and a niobium joint according to claim 1, characterized in that The metal niobium described in step three is the pretreated metal niobium, and the pretreatment is specifically to remove the oxide film on the surface of the metal niobium with 180#, 400# and 800# sandpaper in sequence, and then use ethanol ultrasonic assisted cleaning for 5min to 15min at a power of 50W to 200W; the AgCuTi solder sheet described in step three is the pretreated AgCuTi solder sheet, and the pretreatment is specifically carried out according to the following steps: use 500# sandpaper to polish the AgCuTi solder sheet to remove the surface oxide, and then use ethanol ultrasonic assisted cleaning for 5min to 15min at a power of 50W to 200W.
9. The method of preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing a large-size ceramic matrix composite material and a niobium joint according to claim 1, characterized in that In step 4, vacuum the sample to 1×10 -4 Pa~1×10 -5 Pa.
10. The method of preparing a surface high entropy metallization layer based on Joule thermal shock to assist in brazing a large-size ceramic matrix composite material and a niobium joint according to claim 1, characterized in that In step 4, the temperature is increased to 100°C to 200°C at a heating rate of 5°C / min to 10°C / min, and kept at 100°C to 200°C for 5min to 20min, then increased to 800°C to 950°C at a heating rate of 5°C / min to 10°C / min, and kept at 800°C to 950°C for 5min to 20min, and finally cooled to room temperature at a cooling rate of 5°C / min to 10°C / min.
Citation Information
Patent Citations
Method and device for preparing active metal connecting layer on surface of carbon fiber reinforced silicon carbide composite material matrix
CN112479744A
Diffusion welding method for connecting skutterudite and electrode through high-entropy alloy intermediate layer
CN113828906A
High-entropy alloy and method for repairing tungsten-based powder alloy die-casting die through laser cladding of high-entropy alloy
CN114457272A
Method of joining high entropy alloy, apparatus for joining high entropy alloy, and joined structure of high entropy alloy
US20210245283A1
Method of bonding a ceramic article to a metal article
US4883217A
Cited By
High-temperature-resistant ceramic binder as well as preparation method and application thereof
CN120737805A
High temperature resistant ceramic binder, its preparation method and application
CN120737805B